Development of Local History Teaching Materials Based on Android Integrated Values of Sultan Syarif Kasim II - Pernantah, Piki Setri; Supriatna, Nana; Sariyatun, Sariyatun; Handrianto, Ciptro; Ahmal, Ahmal; Aisiah, Aisiah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to develop android-based digital teaching materials in local history courses at the University of Riau. This Android-based local history teaching material integrates the character values of Sultan Syarif Kasim II which are in accordance with the needs of history education students. This development research uses a 4D model, developed by Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. This research model consists of 4 steps, namely: define, design, develop, and disseminate. The first step is to conduct a preliminary study with a qualitative descriptive approach. The second step is to design an android-based teaching material product. The third step is product printing, product validation by experts, feasibility trials, and product revisions. The fourth step is to disseminate the product so that it can be used as lecture material by students of history education in Faculty of Teacher Training and Education, University of Riau.